2016
DOI: 10.1371/journal.pone.0150690
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Simulated Vitreoretinal Surgery to Prepare Surgeons for the Upcoming Intervention in the Operating Room

Abstract: PurposeTo evaluate the efficacy of the virtual reality training simulator Eyesi to prepare surgeons for performing pars plana vitrectomies and its potential to predict the surgeons’ performance.MethodsIn a preparation phase, four participating vitreoretinal surgeons performed repeated simulator training with predefined tasks. If a surgeon was assigned to perform a vitrectomy for the management of complex retinal detachment after a surgical break of at least 60 hours it was randomly decided whether a warmup tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 25 publications
0
53
0
1
Order By: Relevance
“…In line with this argument, a previous study has shown that warm‐up training for vitreoretinal surgeons on the eyesi before doing real‐life vitreoretinal surgery is effective and gives a better final outcome in the operating room (Deuchler et al. ). In a busy clinical world, the eyesi Simulator is potentially a valuable tool for training and maintaining surgical skills, as it requires only minor supervision from experienced surgeons and enables to achieve better surgical skills.…”
Section: Discussionmentioning
confidence: 74%
“…In line with this argument, a previous study has shown that warm‐up training for vitreoretinal surgeons on the eyesi before doing real‐life vitreoretinal surgery is effective and gives a better final outcome in the operating room (Deuchler et al. ). In a busy clinical world, the eyesi Simulator is potentially a valuable tool for training and maintaining surgical skills, as it requires only minor supervision from experienced surgeons and enables to achieve better surgical skills.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, in vitreoretinal surgery, Deuchler et al. () showed a beneficial effect of warm‐up training on subsequent performance in the OR for both novice and experienced surgeons.…”
Section: Discussionmentioning
confidence: 91%
“…We have shown that our eye surgery simulator has high validation for ILM peeling. However, it is necessary to introduce excellent skill evaluation and scoring methods such as those used in past studies using virtual reality [ 13 15 ]. Besides the video-based dynamic image analysis of the operator, installation of sensor functions in our simulator will allow us to propose a new design of surgical instruments and to construct a validation system.…”
Section: Discussionmentioning
confidence: 99%
“…This membrane is easy to obtain at low cost, but the reproducibility is low because of individual differences and because the film properties do not adequately mimic the natural ILM [ 12 ]. On the other hand, a virtual reality simulator such as the Eyesi (VRmagic, Mannheim, Germany) [ 13 ] has an ILM peeling task, and this simulator provides assessment and feedback of the task to the surgeon [ 13 15 ]. Although such devices are suitable for simulating surgery because of their high reproducibility and lack of ethical problems, obtaining three-dimensional data is often difficult, and extensive time is required to apply the new device to a computer.…”
Section: Introductionmentioning
confidence: 99%